BEST PRACTICE PROGRAM CSR (Corporate Social Responsibility) PT. ASTRA INTERNATIONAL DALAM MEWUJUDKAN KAMPUNG BERSERI ASTRA DI KOTA PEKANBARU - Buana, Panca Dewa; Mashur, Dadang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
Astra Berseri Village is an Astra Sustainable Social Contribution program that is applied to the community with the concept of sustainable development. PT Astra Internasional Tbk as a company in Indonesia created a CSR program called Kampung Berseri Astra (KBA). The CSR program provided by Astra covers 4 aspects, namely education, health, environment and entrepreneurship. This study aims to determine the best practice of Astra's CSR program with its achievement in SDGs and supporting factors of PT. Astra Internasional Tbk in the Astra Berseri Village (KBA) in Pekanbaru City. This study uses the concept of best practice quoting from Eko Prasojo (2004: 4), which explains that there are 3 indicators namely Impact, Partnership, and Sustainability. This type of research uses descriptive methods with a qualitative approach. The data collection method in this study used observation and interviews. As for data analysis using data reduction, data presentation, and drawing conclusions. The results of the first research, showed that the Astra CSR program in Kampung Berseri Astra (KBA) Pekanbaru City was categorized best practice because the program had been well realized and had a positive impact on the people of the Astra Sereri Village in Pekanbaru City. Second, the supporting factors for Astra's CSR best practice program are Communication, Community Participation, facilities and infrastructure. Keywords: Corporate Social Responsibility (CSR) Sustainable Development (SDGs), Best Practices.